Shrinking Goods - Daniel Levy; Avichai Snir (Emory University, 2013)
If producers have more information than consumers about goods' attributes, then they may use non-price (rather than price) adjustment mechanisms and, consequently, the market may reach a new equilibrium even if prices don't change. We study a situation where producers adjust the quantity per package rather than the price in response to changes in market conditions. Although consumers should be indifferent between equivalent changes in goods' prices and quantities, empirical evidence suggests that consumers often respond differently to price changes and equivalent quantity changes. We offer a possible explanation for this puzzle by constructing and empirically testing a model in which consumers incur cognitive costs when processing goods' price and quantity information.
Keywords: L11; L15; L16; M21; M31; M37; M38; K20; E31; D21; D22; D40; D83; 330; Quantity Adjustment; Cognitive Costs of Attention; Information Processing